Applied Metallurgy and Corrosion Control A Handbook for the Petrochemical Industry - Lahiri, Amiya Kumar (Indian Institute of Metals Series,, 2017)
This book serves as a comprehensive resource on metals and materials selection for the petrochemical industrial sector. The petrochemical industry involves large scale investments, and to maintain profitability the plants are to be operated with minimum downtime and failure of equipment, which can also cause safety hazards. To achieve this objective proper selection of materials, corrosion control, and good engineering practices must be followed in both the design and the operation of plants. Engineers and professional of different disciplines involved in these activities are required to have some basic understanding of metallurgy and corrosion. This book is written with the objective of servings as a one-stop shop for these engineering professionals. The book first covers different metallic materials and their properties, metal forming processes, welding, and corrosion and corrosion control measures. This is followed by considerations in material selection and corrosion control in three major industrial sectors, oil & gas production, oil refinery, and fertilizers. The importance of pressure vessel codes as well as inspection and maintenance repair practices have also been highlighted. The book will be useful for technicians and entry level engineers in these industrial sectors. Additionally, the book may also be used as primary or secondary reading for graduate and professional coursework. .